2015
DOI: 10.1242/jeb.119966
|View full text |Cite
|
Sign up to set email alerts
|

Support for the beam focusing hypothesis in the false killer whale

Abstract: The odontocete sound production system is complex and composed of tissues, air sacs and a fatty melon. Previous studies suggested that the emitted sonar beam might be actively focused, narrowing depending on target distance. In this study, we further tested this beam focusing hypothesis in a false killer whale. Using three linear arrays of hydrophones, we recorded the same emitted click at 2, 4 and 7 m distance and calculated the beamwidth, intensity, center frequency and bandwidth as recorded on each array at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 32 publications
1
10
2
Order By: Relevance
“…Our results do not support the conclusions from Kloepper et al (2012) and Kloepper et al (2015), which suggested adaptive focusing of the echolocation beam and hypothesized that the deformation of the melon causes the biosonar beam to focus. They depicted the melon as an acoustic lens analogous to an optical lens.…”
Section: Results and Dicussionscontrasting
confidence: 99%
See 4 more Smart Citations
“…Our results do not support the conclusions from Kloepper et al (2012) and Kloepper et al (2015), which suggested adaptive focusing of the echolocation beam and hypothesized that the deformation of the melon causes the biosonar beam to focus. They depicted the melon as an acoustic lens analogous to an optical lens.…”
Section: Results and Dicussionscontrasting
confidence: 99%
“…Thus, the popular melon focusing notion is not accurate. Second, with respect to the hypothesis mentioned by Kloepper et al (2012) and Kloepper et al (2015), although the recent data reported the biosonar beam property can be changed by the deformation of animal's forehead (Wisniewska et al, 2015), there could be many factors involved in this complex process (not only by the deformation of melon). The deformation is caused by the action of fibers and tendons of the muscles associated with the melon and it would also alter the shape of other soft tissues in animal's forehead such as the connective tissue.…”
Section: Results and Dicussionsmentioning
confidence: 95%
See 3 more Smart Citations